2005
DOI: 10.1539/joh.47.165
|View full text |Cite
|
Sign up to set email alerts
|

Hand Arm Vibration Syndrome among Quarry Workers in Vietnam

Abstract: According to work observation studies, daily exposure time to vibration was 160-210 min. ISO5349 predicted that this exposure level would be associated with a high risk of HAVS in workers. We found no clear evidence of VWF. There may be several reasons why no worker exhibited VWF: (1) warmer work conditions, (2) younger and less experienced workers, (3) seasonal changes in work operations, and (4) healthy worker effect. On the other hand, 5-10% of rock drill operators might be suffering from moderate HAVS whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
6
32
0
1
Order By: Relevance
“…There is a huge gap between this study and both previous studies in terms of job duration. This finding is similar with that reported in Vietnam, Papua New Guinea and Indonesia, which concluded that factors of climate (more than 25°C), young workers and shorter work experience play important roles in reducing the vibrating effect 12,13,[23][24][25] . The final factors in this study was the climate condition 12,13,[23][24][25] .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…There is a huge gap between this study and both previous studies in terms of job duration. This finding is similar with that reported in Vietnam, Papua New Guinea and Indonesia, which concluded that factors of climate (more than 25°C), young workers and shorter work experience play important roles in reducing the vibrating effect 12,13,[23][24][25] . The final factors in this study was the climate condition 12,13,[23][24][25] .…”
Section: Resultssupporting
confidence: 90%
“…This finding is similar with that reported in Vietnam, Papua New Guinea and Indonesia, which concluded that factors of climate (more than 25°C), young workers and shorter work experience play important roles in reducing the vibrating effect 12,13,[23][24][25] . The final factors in this study was the climate condition 12,13,[23][24][25] . Warmer work conditions, which are influenced by the local tropical climate, inhibit the development of vibration-induced white finger 13,[23][24][25] .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Increased prevalence or excess risk for neurosensory disturbances, CTS and/or abnormal sensory testing have been reported in crosssectional studies of HTV-exposed workers carried out in several countries (19)(20)(21). Only few studies have investigated prospectively the occurrence of neurosensory disorders in HTV-exposed workers.…”
Section: Exposure-response Relationship For Vibration-induced Sensorymentioning
confidence: 99%